2010
DOI: 10.1111/j.1365-2915.2010.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antibacterial activity in larvae of the blowflyLucilia sericataby an infected environment

Abstract: Maggot debridement therapy (MDT) is a method for the treatment of intractable, infected and necrotic wounds. In MDT, sterile larvae of Lucilia sericata Meigen (Diptera: Calliphoridae) are applied to infected wounds, where they exert antibacterial effects. Once the larvae are placed in the wound, they are no longer germ-free. This study analysed the influence of infected environments on larval antibacterial activities. Sterile larvae were mixed in a test tube containing a bacterial suspension of Staphylococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 27 publications
1
27
0
2
Order By: Relevance
“…Antimicrobial activity has been seen even against highly antibiotic-resistant bacteria [40, 43] and against the protozoan Leishmania parasite [44, 45]. Kawabata et al [46] demonstrated that the antimicrobial activity could be modified by exposure to microbial challenges (as is the case with many innate immunodefense peptides).…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial activity has been seen even against highly antibiotic-resistant bacteria [40, 43] and against the protozoan Leishmania parasite [44, 45]. Kawabata et al [46] demonstrated that the antimicrobial activity could be modified by exposure to microbial challenges (as is the case with many innate immunodefense peptides).…”
Section: Resultsmentioning
confidence: 99%
“…The inducible nature of larval antibacterial activity had been reported previously, but has also been verified yet again more recently, with results indicating that that infected larvae have much better antibacterial capacities than sterile larvae [7]. Researchers argue that the clinical wound situation would enable larvae in the infected environment to influence production of their antibacterial activities.…”
Section: Advances In Wound Disinfection By Medicinal Maggotsmentioning
confidence: 93%
“…There are many reports showing that the secretions of maggots have anti-bacterial properties (eg. Simmons, 1935;Pavillard and Wright, 1957;Thomas et al, 1999;Kawabata et al, 2010). Kawabata et al (2010) showed that some of these factors are induced in L. sericata by an infected environment.…”
Section: Wound Disinfectionmentioning
confidence: 96%
“…Simmons, 1935;Pavillard and Wright, 1957;Thomas et al, 1999;Kawabata et al, 2010). Kawabata et al (2010) showed that some of these factors are induced in L. sericata by an infected environment. A few of the anti-bacterial factors involved have now been identified and characterised (Table 6).…”
Section: Wound Disinfectionmentioning
confidence: 96%